Effects of inhibiting PI3K-Akt-mTOR pathway on lipid metabolism homeostasis in goose primary hepatocytes. (9th March 2016) - Liu, D. D.; Han, C. C.; Wan, H. F.; He, F.; Xu, H. Y.; Wei, S. H.; Du, X. H.; Xu, F.
Abstract : Phosphatidylinositol-3 kinases (PI3K)-Protein kinase B (Akt)-mammalian target of rapamycin (mTOR) pathway plays an important role in the synthesis and secretion of triacylglycerol. However, the mechanism of PI3K-Akt-mTOR pathway in regulating lipid metabolism of goose liver was poorly understood. The purpose of this study was to determine how PI3K-Akt-mTOR pathway regulating lipid metabolic homeostasis in goose hepatocytes. Goose primary hepatocytes were treated with different PI3K-Akt-mTOR signal inhibitors (LY294002, rapamycin and NVP-BEZ235) for 24 h. The results showed that these inhibitors evidently inhibited PI3K-Akt-mTOR downstream signaling. Meanwhile, these PI3K-Akt-mTOR inhibitors reduced intracellular lipid accumulation, decreased the mRNA expression and protein content of genes involved in the de novo fatty acid synthesis, while increased the transcriptional and protein level of key factors involved in fatty acid oxidation and very low density lipoprotein (VLDL) assembly and secretion. Conclusion: These findings suggested that the reduction of lipids accumulation induced-by inhibiting PI3K-Akt-mTOR pathway was closely linked to the decrease of lipogenesis, the increase of fatty acids oxidation, and the increase of VLDL assembly and secretion in goose hepatocytes.